Early Epidemiological Features of COVID-19 in Nepal and Public Health Response - Dhakal, Santosh; Karki, Surendra (Frontiers in Medicine, 2020)
Coronavirus disease 2019 (COVID-19), caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), was first reported in late 2019 from Wuhan, China. Considering its alarming levels of spread and severity, World Health Organization (WHO) declared a global pandemic of COVID-19 in March 11, 2020. First case of COVID-19 was reported in Nepal in January 23, 2020. The Government of Nepal implemented different public health measures to contain COVID-19, including border closures and countrywide lockdown. We collected the daily data provided by the Ministry of Health and Population (MoHP) of Government of Nepal and illustrated the early epidemiological characteristics of COVID-19 in Nepal. By May 31, 2020, 1,572 cases and 8 deaths were reported in Nepal associated with COVID-19. The estimate of prevalence for COVID-19 among tested population was 2.25% (95% CI: 2.15- 2.37%) and case-fatality rate was 0.5%. The majority of the cases were young males (n= 1454, 92%); with overall average age being 30.5 years (Range: 2 months to 81 years) and were mostly asymptomatic. There were only five cases from three districts until the end of March while cases surged from April and has spread to 57 out of 77 districts of Nepal by the end of May 2020 despite the continuous lockdown. Most of these cases are form the southern plains of Nepal bordering India. As the effect of COVID-19 is expected to persist longer, Government of Nepal should make appropriate strategies for loosening lockdowns in a phase-wise manner while maintaining the social distancing and personal hygiene and increasing its testing, tracking and medical capacity.